New Insights in Bladder Cancer Diagnosis: Urinary miRNAs and Proteins - GÜLLÜ AMURAN, GÖKÇE; TİNAY, İLKER; AKKİPRİK, MUSTAFA (My University, 2018)
Bladder cancer is the 10th-most common cancer worldwide. The diagnosis and follow-up of patients require costly invasive methods and due to these expenses, bladder cancer continues to be one of the expensive malignancies. Early diagnosis is crucial in bladder cancer as it is in other cancers; therefore, non-invasive biomarkers for early diagnosis are very important. In this review, we aimed to focus on the most recent investigations on potential urinary micro RNA (miRNA) and protein biomarkers for bladder cancer diagnosis and their associated pathways. Studies performed by different groups were compiled and the biomarker properties of various proteins and miRNAs in the urine of bladder cancer patients were evaluated. Key studies were obtained by searching keywords "bladder cancer, urinary miRNA, urinary protein, urinary biomarker". Targets and the pathways of the miRNAs and proteins were analyzed according to mirBase Catalogue and Panther Database. The major pathways that are targeted by aberrantly expressed miRNAs are Cholecystokinin receptor (CCKR), p53, Wnt signaling pathway, and feedback loops. We hereby conclude that urinary micro RNAs and proteins are promising candidates for bladder cancer diagnosis. It should be noted that urine collection, storage conditions, choice of fraction, and normalization strategies should be standardized.
Keywords: bladder cancer; cholecystokinin receptor pathway; micro RNA (miRNAs); p53 pathway; urinary biomarkers; urinary proteins